2,500 najpopularniejszych idiomow amerykanskich dla polakow z przykladami w jezyku polskim i angielskim - Lizakowski, Adam.; Marcinkiewicz, Pawel (Chicago, IL : Unpaid Rent Poetry Group, 1996)
A compilation of 2,500 most popular American idioms for Polish speakers, with examples in English and in Polish.
Keywords: English language -- Idioms -- Dictionaries -- Polish